(untitled) - Coovadia, H.M.; H.M. Coovadia; D.F. Wittenberg (Capetown,New York, 1999)
Completely revised and updated to reflect the new focus on primary care in the South African health professions, this popular manual covers all aspects of child care in both First and Third World conditions
Keywords: Children; Children